Analytical solutions of an isothermal two-dimensional model of a cathode flow channel in a proton exchange membrane fuel cell - Thosar, Aniket U.; Lele, Ashish K. (Chemical Engineering Science, 2018)
Two key assumptions are usually made while deriving analytical solutions of coupled kinetics and transport equations in a single channel on the cathode plate of a proton exchange membrane fuel cell (PEMFC). These are: plug flow and uniform oxygen concentration along the depth of the channel. However these assumptions are not always valid under typical operating conditions of a PEMFC, and particularly so at high current density. In this article we relax these two assumptions and present approximate analytical solutions of the governing equations using the methodology of separation of variables followed by power series solution. Spatial profiles of oxygen concentration and current density were derived, which led to the final derivation of a comprehensive current-potential relationship (polarization curve) in the reaction-controlled regime of an operational PEMFC. We compare polarization curves predicted by the present model with predictions of the earlier analytical model and also with a complete 3D-simulation of the same flow geometry and operation conditions. The local profiles of oxygen concentration and the polarization curve predicted by the present model compare far better with the 3D simulations than the earlier analytical model. While this comparison highlights the importance of the effects of finite oxygen diffusion rate and velocity profile in the channel on the polarization curves, it also points to other important factors that affect the current-potential relation.

Analytical solutions of an isothermal two-dimensional model of a cathode flow channel in transport limited operational regimes of a proton exchange membrane fuel cell - Thosar, Aniket U.; Lele, Ashish K. (Chemical Engineering Science, 2019)
In the quest for obtaining accurate closed-form analytical expressions for polarization curve of a proton exchange membrane fuel cell (PEMFC), we have recently presented a two-dimensional model that accounts for oxygen concentration gradient and velocity gradient along the depth of a cathode flow channel. The model was developed for the case when Tafel kinetics of oxygen reduction reaction (ORR) on the cathode governs the overall rate of oxygen consumption. An improved match between predictions of the model and full three-dimensional simulations was obtained over the entire range of current density compared with earlier models which assumed homogenous oxygen concentration in the channel depth and plug flow velocity profile. In reality however, ORR kinetics is often not the rate limiting step for oxygen consumption in the cathode catalyst layer (CCL) at high current density since the Tafel kinetics is modulated by transport resistances in the CCL. In this article, we extend our two-dimensional analytical model to two different transport-limited regimes of CCL operation namely, slow oxygen transport across the CCL and slow proton transport across the CCL. We compare model predictions with results of full three-dimensional simulations in both cases and show that they are in excellent agreement even in these transport limited operational regimes of PEMFC. (C) 2018 Elsevier Ltd. All rights reserved.
Keywords: Analytical modelling; Polarization curve; Proton exchange membrane fuel cells; Transport resistance

Comprehensive analytical model for polarization curve of a PEM fuel cell and experimental validation - Thosar, Aniket U.; Agarwal, Harshal; Govarthan, S.; Lele, Ashish K. (Chemical Engineering Science, 2019)
The kinetics of cathodic oxygen reduction reaction (ORR) in a proton exchange membrane fuel cell (PEMFC) is significantly modulated by the resistances for transport of reactants to the catalytic sites offered by different components of the fuel cell. This modulation governs the polarization curve of the PEMFC. Consequently, the various operating, geometric and material parameters of the fuel cell dictate the polarization curve. The effects of these parameters on the polarization curve over the entire range of current density, from zero to limiting current, can be predicted using detailed numerical simulations, which are however expensive. Analytical models, although simple can capture the essential details of physico-chemical processes occurring inside a PEMFC and are significantly inexpensive. In this article, we derive an analytical equation of the polarization curve which is valid over the entire range of current density. Specifically, the representative situation of a humidified low temperature PEMFC is considered wherein oxygen transport resistance in the cathode catalyst layer (CCL) is encountered at lower current density than proton transport resistance in the CCL. A novel experimental methodology is illustrated to confirm that this is indeed the case. Next, we elucidate a procedure to determine in-situ oxygen diffusion coefficients in the various domains of an operational PEMFC. Finally, it is shown that the analytical polarization curve predicted using these parameters is in excellent agreement with the experimental and numerically simulated polarization curves over the entire range of current density. The significance of this work is that the analytical model relates the performance of a PEMFC to all operating and geometric parameters as well as the average transport and kinetic properties of the materials used in its different components, without the need for computationally expensive numerical simulations. The model can therefore provide useful insights for enhancing the performance of PEMFC in different regimes of current density as well as for diagnostic purposes. (C) 2019 Elsevier Ltd. All rights reserved.
Keywords: Fuel cell equation; Modelling; PEMFC; Polarization curve

Interdigitated flow field impact on mass transport and electrochemical reaction in high-temperature polymer electrolyte fuel cell - Agarwal, Harshal; Thosar, Aniket U.; Bhat, Santoshkumar D.; Lele, Ashish K. (Journal of Power Sources, 2022)
The enhanced performance of Polybenzimidazole (PBI) based high-temperature polymer electrolyte fuel cell (HT-PEFC) with interdigitated flow field over the other flow fields can be a consequence of higher average pressure developed on the flow field due to dead end in the channels or faster mass transport due to pressuredriven convection in the gas diffusion layer (GDL). In the present study, the effect of average pressure on the flow field and mass transport mechanism in the GDL on the HT-PEFC performance have been systematically decoupled. Three-dimensional simulation validated by experimental studies confirm that the enhanced performance in case of the interdigitated flow field is due to faster mass transport in the GDL and not due to higher average gas pressure. The simulation studies are performed on the interdigitated flow field and compared against the parallel flow field to have an insight into the effect of key operating and geometric parameters. There exists an optimum value for channel to rib ratio and current density saturates after an air stoichiometry of 4 which is validated by experiments.
Keywords: HT-PEFC; Interdigitated flow field; Mass transport mechanism; pressure; stoichiometry